A autoavaliação institucional como instrumento de educomunicação a serviço da gestão escolar democrática e participativa - Oliveira, Vanessa Paula de (2021)
This study is linked to the master's program in management and educational practices at University Nove de Julho (PROGEPE – UNINOVE). The object of study proposed was the role of educommunication in the process of institutional self-assessment carried out in kindergarten and elementary school grades, in a public school located in a county in the ABC region of São Paulo. The general objective was to analyze the institutional self-assessment process of the selected school unit, from the perspective of educommunication and participatory management. The following specific objectives were listed: to identify the principles and guidelines used in institutional self-assessment in the researched school unit; identify the specifics of institutional self-assessment and the elements that constitute educommunication in this process; understand what are the possible advances and challenges to be overcome in carrying out the institutional self-assessment. The guiding questions in the development of this research were: can institutional self-assessment from the perspective of educommunication be used as an auxiliary resource to assess the quality of education in the school unit? What are the principles and guidelines for the insertion of institutional self-assessment, from the perspective of participatory management in a kindergarten and elementary school, located in the ABC region? What are the potentials of institutional self-assessment to foster mediation between management and participants in the school community? What are the possibilities and challenges to be overcome so that the realization of an institutional self-assessment is an ongoing and democratic process? The methodology design was to carry out research with the characteristics of a case study, using qualitative and quantitative approaches. Data collection took place through a semi-structured questionnaire through electronic forms and interviews with two representatives of the management team; the director and pedagogical assistant; eight teachers; six employees; and thirteen community participants. The research universe is a kindergarten and elementary school in the city, in the state of São Paulo, in the ABC region and the subjects are community members, teachers, employees, and the management team belonging to the school. The theoretical foundation is supported by authors such as: Heloísa Lück, José Dias Sobrinho, Bernadete Gatti, José Carlos Libâneo, Luís Carlos Freitas, António Nóvoa, Ismar De Oliveira Soares, Nádia Conceição Lauriti, Paulo Freire, João Eustáquio Romão And Martin-Barbero. This research was also guided by searching the official documents relating to basic education and institutional self-assessment. The results obtained indicate advances and challenges to be overcome concerning the insertion of institutional self-assessment, as a continuous and democratic process. In the elementary school, the results indicate that research participants recognize the importance of self-assessment and their active participation in the decision-making processes of the school, endorsed by the dialogic way, but still do not exercise it. It was observed that there are no effective actions for the inclusion of everyone in the self-assessment processes, nor is there a favorable organizational culture for institutional self-assessment, from the perspective of educommunication as a democratic tool in school spaces.